The Effectiveness of Group Guidance Using Self-Monitoring Techniques Assisted by Cybercounseling in Reducing Academic Procrastination Behavior - Anita Nurkhasanah; Dwi Yuwono Puji Sugiharto; Farid Ahmadi (Indonesian Journal of Guidance and Counseling: Theory and Application, 2025)
Academic procrastination remains a fairly common issue among junior high school students. Habits of delaying task completion, poor time management, and low self-awareness in regulating learning behavior contribute to decreased academic performance and student responsibility. This condition calls for appropriate and systematic guidance and counseling interventions. This study aims to analyze the effectiveness of group guidance using self-monitoring techniques in reducing the level of academic procrastination among eighth-grade students of class VIII E at SMPN 7 Cirebon. The study employed a one-group repeated measures design with 7 students selected through purposive sampling. Data were collected using an academic procrastination scale administered before and after the intervention. The results indicate that group guidance using self-monitoring techniques is effective in reducing students’ academic procrastination levels. The implementation of self-monitoring strategies through systematic completion of self-monitoring sheets was able to enhance students’ self-awareness, responsibility, and ability to regulate their learning behavior. This study recommends the use of self-monitoring techniques in group guidance as one strategy to help reduce students’ academic procrastination behavior.